Assessing the Impact of a Hydropower Plant on Changes in the Properties of the Sediment of the Bystrzyca River in Poland - Tomczyk, Paweł; Wiatkowski, Mirosław; Gałka, Bernard; Gruss, Łukasz (Frontiers in Environmental Science, 2022)
This study aimed to assess the impact of a hydropower plant (HP) on the Bystrzyca River (left tributary of the Odra River, Poland) on selected parameters of the bottom sediment within this hydrotechnical structure. The following parameters were examined as part of the analyses: particle size distribution, pH, electrical conductivity (EC), and concentrations of Cd, Cu, Cr, Ni, Pb and Zn . Field studies were carried out upstream and downstream of the HP and at reference points. In addition, the risk of heavy metals in aquatic organisms was assessed using an ecotoxicological method. Based on the Wilcoxon signed-rank test, it was found that the HP influenced all of the parameters tested, except pH. Comparing the points closest to and downstream of the HP, an increase in the average grain diameter of D50 (on average by 750%), and a decrease in the concentrations of most heavy metals: Ni (271%), Zn (216%), Cu (163%), Cr (83.0%), and Cd (74.2%), was observed. The ecotoxicological classification of heavy metal concentrations in sediments indicates, in most cases, little or no impact on aquatic organisms; the values of Ni and Zn in some samples upstream of the HP are exceptions, where remediation using synthetic zeolites, metal accumulation plants, or by electrokinetic methods, is necessary. Fine-grained fractions dominate the clays and sandy clays upstream of the hydropower plants, while sands, sandy clay loams, or sandy clays are dominated downstream. Frequent occurrence of skeletal fractions (>2.0 mm) was observed downstream, i.e., an average of 23.30% in each sample compared to 1.82% upstream of the HP, which is mainly due to greater anthropogenic pressure, especially tourism. The dominance of fine-grained fractions upstream of the HPs favors the accumulation of metals due to the high sorption capacity of these fractions. When comparing the analyzed groups of points, the average pH values are arranged in the following sequence: upstream HP (U) > downstream HP (D) > reference points (R), while EC has opposite values (i.e., U